Adaptação transcultural e reprodutibilidade de questionário para avaliação de conhecimento e atitude de profissionais de atenção primária à saúde frente a casos de abuso físico infantil - Fernando Henrique da Silva Oliveira (2012)
The Child Welfare Information Gateway (2008) and the World Health Organization (WHO, 1999) divide abuse into four categories: physical child abuse, neglect, sexual abuse and emotional or psychological abuse. Physical child abuse is defined as an actual or potential physical harm to a child by means of an interaction, or lack of interaction, practiced by the parents, caregivers, guardians or people in positions of responsibility, trust or power (WHO, 1999). The prevalence of physical child abuse reaches alarming numbers in several countries worldwide (CWIG, 2011, UNICEF, 2005). According to the study Child maltreatment, 2010 (CWIG, 2011), the majority of the notifications of child abuse in the United States were made by professionals, 58.6%, and 12.8% of these notifications were made by healthcare professionals. This finding highlights the importance of these professionals in recognizing and reporting child abuse cases. Therefore, assessing knowledge and attitudes of healthcare professionals regarding cases of physical child abuse is of great value in order that public health measures are taken aiming to increase notifications of abuse and hence curbing this social stigma. A major limitation that seems to exist in the studies of knowledge, perception and attitudes of healthcare professionals regarding cases of child abuse, conducted in Brazil, is the uncertainty concerning the methodology applied, for example, when referring to the measuring instruments applied, once they often are not validated methods, or at least it is not reported in the articles data stating whether the research tools were submitted to validation methods or not (Luna et al, 2010; Azevedo et al., 2012). The aim of this study was to carry out a cross-cultural adaptation of questionnaire developed to assess knowledge, experience and attitude of primary healthcare professionals concerning physical child abuse cases, developed at the University of London (Lazenbatt and Freeman, 2006) and subjected to face validity. To perform the transcultural adaptation it was carried out the translation of the instrument, following the methods described by Herdman (1998). The questionnaire was administered to 107 professionals from the teams of the Family Health Strategy (FHS) of Belo Horizonte, Minas Gerais, as well as professionals from the FHS support teams. The first translated version of the questionnaire was subjected to test-retest on two occasions, first among 21 professionals and a second time among 32 professionals. Data were analyzed using SPSS, version 17.0. Most of the questions were excellent values for the tests Kappa and Weighted Kappa above 80%. The Brazilian version of the questionnaire evaluating the knowledge and attitudes of healthcare professionals in relation to physical child abuse showed great values relating to the kappa and weight kappa tests for the majority of the questions proving the method to be reliable, accurate and reproducible for use in Brazilian primary healthcare professionals